Sound-absorbing dehumidifying rotating wheel and preparation method thereof
By combining lightweight and high -liquidity sound -absorbing coatings with glass fiber dehumidification rotor, and using microwave rapid solidification technology, the problem of high noise and cost of dehumidifier is solved, and a significant mute effect and reducing cost effects are achieved.
Patent Information
- Application Number
- CN202310918220.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
The noise problem of existing dehumidifiers is difficult to effectively solve. The traditional shock-absorbing and noise-reducing devices have complex structures, high cost and poor results. Ordinary sound-absorbing coatings have high viscosity and are difficult to apply and easily block the wheel.
The light -quality high -liquidity sound -absorbing coatings are combined with the glass fiber dehumidification rotor to prepare sound -absorbing and dehumidifying wheels through pre -processing, impregnated reactions, washing, and baking. The microwave rapid solidification is performed after coating to improve the solidification efficiency.
Effectively reduce the noise of dehumidifier, the mute effect is significantly better than the national standard requirements, solve the root cause of the noise problem, and reduce the processing difficulty and cost of the dehumidifier.
Smart Images

Figure CN119371856A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dehumidification wheels, and in particular relates to a sound-absorbing dehumidification wheel and a preparation method thereof. Background Art
[0002] The evaluation criteria for noise are usually subjective. All sounds that affect others can be considered noise. From the perspective of environmental protection, all "unwanted sounds" that affect people's normal study, work and rest in certain occasions can be collectively referred to as noise. From a physical perspective, noise refers to all irregular signals, which are irregular mechanical waves, such as electromagnetic noise, thermal noise, noise during radio transmission, laser noise, fiber optic communication noise, and noise on the screen when a camera takes a picture. Vibration and noise have different propagation pathways and different control methods, but both can be treated with vibration reduction and noise reduction materials. According to the different propagation pathways, control objects and functions, vibration reduction and noise reduction materials can be divided into damping materials, sound insulation materials, vibration isolation materials and sound absorbing materials. Because sound absorbing materials have simple production processes and excellent product characteristics, they have been widely used. Sound absorbing materials mainly use the porous structure in the material to absorb sound waves. When sound waves are incident on these holes, the pores, air and fibers in the slits of the material will vibrate. Due to friction and viscous resistance and the thermal conductivity of the fiber, part of the sound energy is converted into heat energy and dissipated.
[0003] The rotary dehumidifier uses the dehumidification wheel to rotate and circulate to absorb and desorb to dehumidify. The noise caused by the wheel friction, internal transmission and motor is inevitable, which seriously affects the physical and mental health of the user. In addition, the vibration generated when the dehumidifier is working causes the dehumidifier to shake more, which leads to loose parts inside the dehumidifier, and thus poor stability. At present, in order to solve the noise problem of dehumidifiers, it is generally chosen to add additional shock-absorbing and noise-reducing devices to the dehumidifier. The structure of this device is very complex, and it is extremely difficult to design and process. The poor noise reduction effect greatly increases the cost. On this basis, the idea of combining sound-absorbing coatings with rotors was proposed, but ordinary sound-absorbing coatings have high viscosity, are difficult to apply, and are easy to clog the rotor.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a sound-absorbing dehumidification wheel and a preparation method thereof to solve the above-mentioned problems.
[0006] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0007] A method for preparing a sound-absorbing dehumidification wheel, comprising:
[0008] The glass fiber dehumidification wheel is pretreated, then immersed in a reaction solution in a stirring state to react, then washed to neutrality, dehydrated, and calcined to obtain a dehumidification wheel matrix;
[0009] The acrylic emulsion, acrylic resin, propylene glycol and additives are mixed and dispersed for the first time, and then mixed powder of heavy calcium, quartz and mica is added to perform a second dispersion, and the mixture is allowed to stand to obtain a sound-absorbing coating;
[0010] The sound-absorbing coating is applied to the dehumidification wheel substrate and cured to obtain the dehumidification wheel substrate;
[0011] Wherein, the calcination temperature is 120-150°C and the calcination time is 3-5h.
[0012] Preferably, the calcination temperature is 130° C. and the calcination time is 4 hours. Too high a temperature may easily damage the adsorbent, while too low a temperature may be detrimental to activation.
[0013] Optionally, the preprocessing satisfies one or more of the following conditions:
[0014] a. The pretreatment is to immerse the glass fiber dehumidification wheel in water glass, repeatedly pull and immerse, remove excess water glass and then dry; remove excess water glass to prevent clogging;
[0015] b. The concentration of the water glass is 25%-35%;
[0016] Preferably, the concentration of water glass is 30%;
[0017] c. The drying temperature is lower than 80°C.
[0018] Optionally, the reaction satisfies one or more of the following conditions:
[0019] d. The preparation of the reaction solution comprises diluting concentrated sulfuric acid and adjusting the pH value to 1-3; preferably, the optimal pH value is 2;
[0020] e. The reaction is carried out in a water bath;
[0021] f. The temperature of the water bath is 30-70 ° C; preferably, the temperature of the water bath is 50 ° C;
[0022] g. The reaction time is 2-4 hours; preferably, the reaction time is 3 hours.
[0023] Optionally, the auxiliary agent includes a dispersant, a flame retardant, and a defoaming agent; preferably, the dispersant is polyethylene glycol; preferably, the flame retardant is ammonium polyphosphate; preferably, the defoaming agent is polydimethylsiloxane;
[0024] Preferably, the ratio of the dispersant, flame retardant and defoamer is 1-1.5:3-4:1;
[0025] Preferably, the ratio of the acrylic emulsion, acrylic resin, propylene glycol and the auxiliary agent is 28-32:2.5-3.5:1:5-7.
[0026] Optionally, the first dispersion and the second dispersion are performed using a high-speed disperser;
[0027] Preferably, the first dispersing speed is 300-400 r / min, and the dispersing time is 10-20 min; further, the first dispersing speed is 300 r / min, and the dispersing time is 15 min;
[0028] Preferably, the second dispersion speed is 800-1000 r / min, and the dispersion time is 20-30 min; further, the second dispersion speed is 1000 r / min, and the dispersion time is 25 min;
[0029] Preferably, the standing time is 18-30 hours. Further, the standing time is 24 hours.
[0030] Optionally, the particle size of the mixed powder is less than or equal to 1 mm;
[0031] Preferably, in the mixed powder, the ratio of heavy calcium, quartz and mica is 3.5-4:2-3:1.
[0032] The sound-absorbing coating applied to the dehumidification wheel needs to have high fluidity in addition to being lightweight, which is more conducive to coating. Different from ordinary sound-absorbing coatings, the sound-absorbing coating prepared in the present invention has improved fluidity by reducing the proportion of heavy calcium, quartz and mica powder, and its particle size is optimized, which overcomes the technical problem that the honeycomb holes of the wheel are easily blocked due to overly large particles.
[0033] Optionally, the curing temperature is 120-140° C. and the curing time is 90-150 min.
[0034] Preferably, the curing temperature is 120° C. and the curing time is 120 min.
[0035] Optionally, the method further comprises, before the coating, uniformly mixing the sound-absorbing coating with silica sol, and then coating;
[0036] Preferably, the usage ratio of the sound absorbing coating to the silica sol is 80-100:10-20.
[0037] Adding silica sol to the formula helps the substrate to bond with the sound insulation coating, prolongs its service life and reduces the risk of the sound insulation material falling off.
[0038] Optionally, the method further comprises subjecting the coated product to microwave treatment before the curing;
[0039] Preferably, the microwave power is 80-120W and the time is 20-40min.
[0040] Furthermore, the power of the microwave is 100W and the time is 30min.
[0041] Microwaves are used before curing, and microwaves are used to quickly cure after coating to prevent the coating from flowing on the substrate, and then it is slowly dried. In addition, the curing temperature is lower than the operating temperature of the wheel, which avoids damage to the wheel during the drying process.
[0042] The invention also provides a sound-absorbing dehumidifying rotary wheel, which is prepared by the preparation method.
[0043] A lightweight and highly fluid sound-absorbing coating is applied to the surface of the impeller. The coating has a low thickness and has little effect on the wind resistance and dehumidification capacity of the impeller surface. When used in a dehumidifier, it can effectively absorb internal sound waves, especially the noise caused by friction at the impeller can be solved from the source.
[0044] Beneficial effects of the present invention:
[0045] The present invention adopts the form of directly combining the sound-absorbing material with the dehumidification wheel, which does not need to change the structural design of the dehumidifier itself, greatly reduces the processing difficulty and cost of the dehumidifier, and the lightweight sound-absorbing coating is combined with the wheel to obtain a dehumidification wheel with sound absorption effect, thereby overcoming the noise problem of the existing dehumidification wheel when used in an indoor environment.
[0046] Tests have proven that the vibration and noise generated during the operation of the impeller can be promptly absorbed by the sound-absorbing film on the surface of the impeller. The noise-reducing effect is significantly better than the requirements of national standards, and the effect of solving the problem at the root is particularly obvious. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1 This is a schematic diagram of the surface of the sound-absorbing dehumidification wheel prepared in Example 1. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0050] Example 1
[0051] According to the method provided by the present invention, a sound-absorbing dehumidification wheel is prepared, and the specific steps are as follows:
[0052] S1: pre-treat the glass fiber dehumidification wheel by immersing it in 30% water glass at room temperature, remove excess water glass after repeated pulling and immersion, and dry it at below 80°C;
[0053] S2: dilute the concentrated sulfuric acid and adjust the pH to 2, and use it as the reaction solution. Immerse the wheel obtained in S1 in the reaction solution in a 50°C water bath, ensure that the reaction solution is constantly stirred, and react for 3 hours;
[0054] S3: removing excess reaction liquid from the wheel obtained in S2, washing with deionized water until the effluent is neutral, drying and calcining at 130° C. for 4 h to obtain a dehumidification wheel substrate;
[0055] S4: 38g acrylic emulsion, 3g acrylic resin, 1.25g propylene glycol, 1.25g dispersant, 3.75g flame retardant, and 1g defoamer were uniformly dispersed in a high-speed disperser at a speed of 300r / min for 15min to obtain a precursor of a sound-absorbing coating;
[0056] S5: Grind 75g of heavy calcium, 50g of quartz and 20g of mica powder to a particle size of less than 1mm, then add them to the coating precursor obtained in S4, and disperse them evenly in a high-speed disperser at a speed of 1000r / min for 25min. After standing for 24h, a highly fluid lightweight sound-absorbing coating is obtained;
[0057] S6: 90g of the sound-absorbing coating obtained in step S5 and 15g of silica sol are mixed evenly and then coated on the front and rear surfaces of the dehumidification wheel substrate obtained in S3, first microwaved at 100W for 30min, then dried and cured at 120°C for 120min, to obtain a composite silica gel sound-absorbing dehumidification wheel that can absorb sound waves and reduce noise, which is denoted as sound-absorbing dehumidification wheel A. Its surface schematic diagram is shown in Figure 1 As shown, the coating is evenly coated on the entire surface of the rotor and the channel.
[0058] Example 2
[0059] According to the method provided by the present invention, a sound-absorbing dehumidification wheel is prepared, and the specific steps are as follows:
[0060] S1: pre-treat the glass fiber dehumidification wheel by immersing it in 30% water glass at room temperature, remove excess water glass after repeated pulling and immersion, and dry it at below 80°C;
[0061] S2: dilute the concentrated sulfuric acid and adjust the pH to 2, and use it as the reaction solution. Immerse the wheel obtained in S1 in the reaction solution in a 50°C water bath, ensure that the reaction solution is constantly stirred, and react for 3 hours;
[0062] S3: removing excess reaction liquid from the wheel obtained in S2, washing with deionized water until the effluent is neutral, drying and calcining at 130° C. for 4 h to obtain a dehumidification wheel substrate;
[0063] S4: 35 g acrylic emulsion, 3 g acrylic resin, 1.25 g propylene glycol, 1.25 g dispersant, 3.75 g flame retardant, and 1 g defoamer were uniformly dispersed in a high-speed disperser at a speed of 300 r / min for 15 min to obtain a precursor of a sound-absorbing coating;
[0064] S5: Grind 75g of heavy calcium, 50g of quartz and 20g of mica powder to a particle size of less than 1mm, then add them to the sound-absorbing coating precursor prepared in S4, and disperse them evenly in a high-speed disperser at a speed of 1000r / min for 25min. After standing for 24h, a highly fluid and lightweight sound-absorbing coating is obtained;
[0065] S6: Mix 90g of the sound-absorbing coating obtained in step S5 and 10g of silica sol evenly, and then apply the mixture on the front and rear surfaces of the dehumidification wheel substrate obtained in step S3. First, microwave it at a power of 100W for 30min, and then dry and cure it at 120°C for 120min to obtain a composite silica gel sound-absorbing dehumidification wheel that can absorb sound waves and reduce noise, which is recorded as sound-absorbing dehumidification wheel B.
[0066] Example 3
[0067] The difference from Example 1 is that:
[0068] The concentration of water glass in S1 is 25%;
[0069] The amount of acrylic emulsion in S4 is 40 g;
[0070] The silica sol in S6 is 20 g, and the obtained product is recorded as sound-absorbing dehumidification wheel C.
[0071] Example 4
[0072] The difference from Example 2 is that:
[0073] The concentration of water glass in S1 is 25%;
[0074] The product obtained from S6 is recorded as sound-absorbing dehumidification wheel D.
[0075] Example 5
[0076] The difference from Example 1 is that in step S6, 90g of the sound-absorbing coating obtained in step S5 is directly coated on the front and rear surfaces of the dehumidification wheel substrate obtained in S3, first microwaved at a power of 100W for 30min, and then dried and cured at 120°C for 120min to obtain a composite silica gel sound-absorbing dehumidification wheel that can absorb sound waves and reduce noise, which is recorded as sound-absorbing dehumidification wheel E.
[0077] Example 6
[0078] The difference from Example 1 is that in step S6, 90g of the sound-absorbing coating obtained in step S5 is evenly mixed with 15g of silica sol and then coated on the front and rear surfaces of the dehumidification wheel substrate obtained in S3, and then dried and cured at 120°C for 120 minutes to obtain a composite silica gel sound-absorbing dehumidification wheel that can absorb sound waves and reduce noise, which is recorded as sound-absorbing dehumidification wheel F.
[0079] The parameters of the sound-absorbing dehumidification wheels prepared in Examples 1-6 are shown in Table 1 below:
[0080] Table 1 Parameters of the sound-absorbing dehumidification wheels obtained in Examples 1-6
[0081] project Coating thickness Coating Depth Paint viscosity Example 1 2.1mm 3.1mm 12000mpa*s Example 2 2.9mm 3.5mm 15000mpa*s Example 3 1.7mm 2.9mm 10000mpa*s Example 4 2.8mm 3.6mm 15000mpa*s Example 5 1.7-2.0mm 2.8mm 12000mpa*s Example 6 1.8mm 3.2-3.7mm 12000mpa*s
[0082] It can be seen from Table 1 that the coating viscosity of the sound-absorbing dehumidification wheel A in Example 1 is moderate, and the coating thickness and depth are uniform; the amount of emulsion is reduced during the preparation process of Example 2 and Example 4, the coating viscosity is increased, the coating amount is increased, and the coating thickness is slightly increased; the amount of emulsion in the sound-absorbing dehumidification wheel C in Example 3 is increased, and the corresponding wheel coating amount is low, and the coating thickness is relatively low; in Example 5, since silica sol is not used, the bonding ability of the coating and the substrate is reduced, the coating falls off during the experiment, the coating thickness is unevenly distributed, and the coating depth is low; in Example 6, microwave rapid curing is not used, which causes the coating to flow during the drying process, and the final coating thickness is low and the coating depth is uneven.
[0083] Comparative Example 1
[0084] Preparation of a dehumidification wheel without sound absorbing material coating:
[0085] S1: pre-treat the glass fiber dehumidification wheel by immersing it in 30% water glass at room temperature, remove excess water glass after repeated pulling and immersion, and dry it at below 80°C;
[0086] S2: dilute the concentrated sulfuric acid and adjust the pH to 2, and use it as the reaction solution. Immerse the wheel obtained in S1 in the reaction solution in a 50°C water bath, ensure that the reaction solution is constantly stirred, and react for 3 hours;
[0087] S3: Remove excess reaction liquid from the wheel obtained in S2, wash with deionized water until the effluent is neutral, dry and calcine at 130°C for 4h to obtain a dehumidification wheel.
[0088] The performance tests were conducted on the wheels prepared in Examples 1-6 and Comparative Example 1, as follows:
[0089] 1. Static water absorption test
[0090] The wheel samples prepared in Examples 1-6 were dried at 120° C. for 2 h and then placed in a fixed temperature and humidity environment. The weight change was recorded at regular intervals and the weight gain rate, i.e., the water absorption rate, was calculated. The test results are shown in Table 2 below.
[0091] Table 2 Static water absorption test results of the runners prepared in Examples 1-6
[0092]
[0093] As can be seen from Table 2, the adsorption performance of samples in Examples 1-6 is at a relatively high level, and the sound-absorbing coating applied on the adsorbent does not have a significant effect on the moisture absorption capacity of the rotor. Example 1 has excellent adsorption rate and adsorption capacity. Example 2 has a relatively high coating coating rate due to the high viscosity of the coating, which affects the moisture absorption and adsorption capacity. Examples 3 and 4 have low water glass concentrations and low adsorbent proportions, and the adsorption capacity is relatively low. Among them, Example 4 has a further decrease in adsorption performance due to the high viscosity of the coating. The adsorption performance of Example 5 is slightly lower than that of Example 1, because silica sol is not used in Example 5. The main function of silica sol is to reduce the risk of sound-absorbing coating falling off, maintain the stability of the combination of the coating and the substrate, maintain the sound absorption performance, and have a relatively small effect on water absorption. Therefore, whether or not silica sol is used will mainly affect the coating amount of the final product, that is, the sound absorption and noise reduction performance. The water absorption performance of Example 6 is quite different from that of Example 1, because the role of microwaves is mainly to prevent the coating from excessively covering the substrate, and the water absorption performance of the covered substrate will be greatly affected. Therefore, microwave treatment has a greater impact on the water absorption performance, that is, the dehumidification capacity. Example 6 also verifies this point. After the microwave is cancelled, the coating depth becomes larger, and the coating covers the substrate too much, which greatly affects the water adsorption capacity.
[0094] 2. Sound absorption and noise reduction performance test
[0095] The dehumidifiers equipped with the rotors of Examples 1-6 and Comparative Example 1 were tested with reference to national standards GB / T 3222.2-2002 and GB 22337-2008. The test environment was divided into Class A room - ordinary bedroom, Class B room - ordinary study, and the test time and temperature were 25°C during the day (12:00-13:00) and 20°C at night (21:00-22:00). With reference to standards GB12348-2008 and GB22337-2008, a HNT16040 sound level meter was selected as the test instrument. The test results are shown in Table 3 below:
[0096] Table 3 Test results of sound absorption and noise reduction of the wheels prepared in Examples 1-6 and Comparative Example 1
[0097]
[0098]
[0099] It can be seen from Table 3 that, referring to the provisions of the national standard GB22337-2008 on environmental noise, when the dehumidifier equipped with the sound-absorbing dehumidification wheel provided by the present invention is in operation, the noise intensity in the room is significantly lower than that in comparative example 1 and the national standard, and a more comfortable environment can be created when used in bedrooms, study rooms and other places.
[0100] Meanwhile, in Example 5, no silica sol is added, the coating is not firmly bonded, the effective coating amount is low, and the sound absorption capacity is poor; in Example 6, the use of microwaves focuses on preventing the coating from excessively covering the runner and affecting the water absorption performance, so the sound absorption performance is less damaged.
[0101] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a sound-absorbing dehumidification wheel, characterized in that: include: The glass fiber dehumidification wheel is pretreated, then immersed in a reaction solution in a stirring state to react, then washed to neutrality, dehydrated, and calcined to obtain a dehumidification wheel matrix; The acrylic emulsion, acrylic resin, propylene glycol and additives are mixed and dispersed for the first time, and then mixed powder of heavy calcium, quartz and mica is added to perform a second dispersion, and the mixture is allowed to stand to obtain a sound-absorbing coating; The sound-absorbing coating is applied to the dehumidification wheel substrate and cured to obtain the dehumidification wheel substrate; Wherein, the calcination temperature is 120-150°C and the calcination time is 3-5h.
2. The preparation method according to claim 1, characterized in that: The pre-processing satisfies one or more of the following conditions: a. The pretreatment is to immerse the glass fiber dehumidification wheel in water glass, repeatedly pull and immerse, remove excess water glass and then dry; b. The concentration of the water glass is 25%-35%; c. The drying temperature is lower than 80°C.
3. The preparation method according to claim 1, characterized in that: The reaction satisfies one or more of the following conditions: d. The preparation of the reaction solution comprises diluting concentrated sulfuric acid and adjusting the pH value to 1-3; e. The reaction is carried out in a water bath; f. The temperature of the water bath is 30-70 ° C; g. The reaction time is 2-4h.
4. The preparation method according to claim 1, characterized in that: The auxiliary agents include dispersants, flame retardants and defoamers; Preferably, the dispersant is polyethylene glycol; Preferably, the flame retardant is ammonium polyphosphate; Preferably, the defoaming agent is polydimethylsiloxane; Preferably, the ratio of the dispersant, flame retardant and defoamer is 1-1.5:3-4:1; Preferably, the ratio of the acrylic emulsion, acrylic resin, propylene glycol and the auxiliary agent is 28-32:2.5-3.5:1:5-7.
5. The preparation method according to claim 1, characterized in that: The first dispersion and the second dispersion are performed using a high-speed disperser; Preferably, the first dispersion speed is 300-400 r / min, and the dispersion time is 10-20 min; Preferably, the second dispersion speed is 800-1000r / min, and the dispersion time is 20-30min; Preferably, the standing time is 18-30 hours.
6. The preparation method according to claim 1, characterized in that: The particle size of the mixed powder is less than or equal to 1 mm; Preferably, in the mixed powder, the ratio of heavy calcium, quartz and mica is 3.5-4:2-3:
1.
7. The preparation method according to claim 1, characterized in that: The curing temperature is 120-140° C. and the curing time is 90-150 min.
8. The preparation method according to claim 1, characterized in that: The method further comprises, before the coating, uniformly mixing the sound absorbing coating with silica sol and then coating; Preferably, the usage ratio of the sound absorbing coating to the silica sol is 80-100:10-20.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The method further comprises subjecting the coated product to microwave treatment prior to the curing; Preferably, the microwave power is 80-120W and the time is 20-40min.
10. A sound-absorbing dehumidification wheel, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.